Initiation with menthol cigarettes and youth smoking uptake. (18th October 2012) - Nonnemaker, James; Hersey, James; Homsi, Ghada; Busey, Andrew; Allen, Jane; Vallone, Donna
Abstract Aims We aimed to assess whether young people who first tried menthol cigarettes were at greater risk of becoming established smokers and dependent on nicotine than young people who started smoking non‐menthol cigarettes. Design Cohort study using data from the American Legacy Longitudinal Tobacco Use Reduction Study (ALLTURS), a three‐wave longitudinal school‐based survey of middle school and high school students. Regression methods were used to assess the association between initiation with menthol cigarettes on risk of transitioning to established smoking or quitting from a non‐smoking state at baseline and on nicotine dependence score at wave 3. Setting The study was conducted in 83 schools in seven communities and five states in the United States. Participants Analyses were restricted to youth who participated in all three waves of ALLTURS, were younger than age 17 at baseline, and had initiated smoking during waves 1 or 2 of the study. Measurements Outcomes were indicators of a transition to established smoking or non‐smoking from non‐established smoking and a nicotine dependence score. The key explanatory variables were an indicator of initiation with menthol cigarettes and indicators for pattern of menthol use over time. Findings Initiating smoking with menthol cigarettes was associated with progression to established smoking [odds ratio (OR) = 1.80, confidence interval (CI): 1.02–3.16] and higher levels of nicotine dependence (β = 1.25, CI: 0.1–2.4). Conclusion Young people in the United States who start smoking menthol cigarettes are at greater risk of progression to regular smoking and nicotine dependence than are young people who start smoking non‐menthol cigarettes.